The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/alz.12637
|View full text |Cite
|
Sign up to set email alerts
|

The apathy, gait impairment, and executive dysfunction (AGED) triad vascular variant

Abstract: Apathy, gait disturbances, and executive dysfunction (AGED) often occur together. Although they can arise independently, the presence of one might portend another. This recognition suggests the possible etiology. We focus on the most common, the vascular. We explain the AGED vascular mechanism through the ambibaric brain concept. The brain contains two complementary blood pressure systems: One high in the primitive brain (brainstem, basal ganglia, and thalamus) and a low‐pressure system in the Homo sapiens bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Cai et al showed the association between MRI findings and apathy, such that lacunar infarcts, CMBs, and severe WMH were detected in patients with apathy (Cai et al, 2022). Hypertension and blood pressure fluctuations can cause damage to brain connections and are associated with white matter disruption, apathy and depression (Hachinski et al, 2022). Moreover, both hypertension and CAA have been associated with apathy (Smith et al, 2021), indicating that small-vessel lesions may also be associated with apathy.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al showed the association between MRI findings and apathy, such that lacunar infarcts, CMBs, and severe WMH were detected in patients with apathy (Cai et al, 2022). Hypertension and blood pressure fluctuations can cause damage to brain connections and are associated with white matter disruption, apathy and depression (Hachinski et al, 2022). Moreover, both hypertension and CAA have been associated with apathy (Smith et al, 2021), indicating that small-vessel lesions may also be associated with apathy.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, the brain circuits such as the frontal regions with their projections to the prefrontal regions, the basal ganglia, the parietal regions, and the anterior cingulate, which play key roles in planning, motivation, and autoactivation, could be injured in CSVD ( Wouts et al, 2020 ). More recently, apathy, combined with gait impairment and executive dysfunction, was conveyed as a new vascular triad in patients with CSVD by Hachinski et al (2022) . Hypertension, cerebral hypoperfusion, white matter tract disconnection, and other CSVD etiological factors were reported to cause apathy ( Moretti et al, 2015 ; Tay et al, 2019 ; Hachinski et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, apathy, combined with gait impairment and executive dysfunction, was conveyed as a new vascular triad in patients with CSVD by Hachinski et al (2022) . Hypertension, cerebral hypoperfusion, white matter tract disconnection, and other CSVD etiological factors were reported to cause apathy ( Moretti et al, 2015 ; Tay et al, 2019 ; Hachinski et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In older adults, depression sometimes manifests as apathy and often occurs concomitantly with gait disorders and executive dysfunction. 12 In older adults with progressive cerebrovascular disease, one encounters the triad of cognitive impairment, lower body Parkinsonism, and depression. A further example of the association between mental and brain health links obsessive compulsive disorder (OCD) with an increased risk of developing an ischemic stroke.…”
Section: Mental Disorders and Vascular Diseasementioning
confidence: 99%